Outside Front Cover: Plasma Process. Polym. 10/2022. Issue 10 (4th October 2022) - Kim, Jinhong; Mironov, Andrey E.; Cho, Jin H.; Sievers, Dane S.; Herring, Cyrus M.; Park, Sehyun; Sun, Peter P.; Liang, Zhihu; Chen, Wenyuan; Park, Sung‐Jin; Eden, J. Gary
Abstract : Outside Front Cover : Photograph of the face of a vacuum ultraviolet (VUV)‐emitting lamp reflected by a 15 cm (6") diameter silicon wafer. Having a radiating area of 100 cm 2, the lamp is the optical source for a commercial VUV photolithography system, manufactured by Cygnus Photonics, with which polymers serve as a dry photoresist. Its peak emission wavelength of 172 nm allows for photopatterning of polymers and cellulose with 10 nm depth precision. Further details can be found in the article by Jinhong Kim, Andrey E. Mironov, Jin H. Cho, Dane S. Sievers, Cyrus M. Herring, Sehyun Park, Peter P. Sun, Zhihu Liang, Wenyuan Chen, Sung‐Jin Park, and J. Gary Eden (e2200075 )